Discoveries from La Manche: Five Years of Early Prehistoric Research in the Channel Island of Jersey. Issue 1 (23rd November 2015) - Pope, Matt; Scott, Beccy; Mills, Josie; Bates, Martin; Bates, Richard; Blinkhorn, Ed; Conneller, Chantal; Duffy, Sarah; Julien, Marie-Anne; Ravon, Anne-Lyse; Shaw, Andrew
Abstract : Since 2010 a new field project drawn from major UK institutions including the UCL Institute of Archaeology, has focused research on the Palaeolithic and Mesolithic record of the Channel Island of Jersey. In this retrospective of five years of research the history of the project to date, its focus on the Middle Palaeolithic site of La Cotte de St Brelade and its growth into an international research team is charted. The formation of the La Manche Prehistorique research network in 2015 marks a new chapter in the development of this project. With its wider focus, but continued commitment to research in the Channel Islands, the research group are working towards a unified early prehistoric research framework for the English Channel region.